The relationship between vertical jump height and residual force depression in knee extensors - Jo, I.; Lee, H.-D. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study investigated the relationship between vertical jump performance and history-dependent muscle force depression. Maximum isometric knee extension torque was measured following a stretch-shortening cycle (SSC) or shortening-only (SHO) contraction and compared to a reference isometric contraction (ISO) at 20°. Residual force depression (rFD) was observed as 14.5% after SSC and 4.9% after SHO. Squat jump (SJ) height was positively correlated with peak concentric torque in the SHO-ISO condition, whereas countermovement jump (CMJ) height showed no significant relationship. Both jump heights showed strong positive correlations with rFD, suggesting that individuals with greater rFD tended to achieve higher jump performance. These findings suggest that rFD may serve as a potential indicator of neuromuscular function in tasks related to SSC.